2019
DOI: 10.1177/0300060519882550
|View full text |Cite
|
Sign up to set email alerts
|

Reduction and fixation of anterior inferior tibiofibular ligament avulsion fracture without syndesmotic screw fixation in rotational ankle fracture

Abstract: Objective We aimed to present the radiographic and functional outcomes of anatomical reduction and fixation of anterior inferior tibiofibular ligament (AITFL) avulsion fracture without syndesmotic screw fixation in rotational ankle fracture. Methods We retrospectively reviewed 66 consecutive patients with displaced malleolar fracture combined with AITFL avulsion fracture. We performed reduction and fixation for the AITFL avulsion fracture when syndesmotic instability was present after malleolar fracture fixati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 54 publications
(107 reference statements)
0
15
0
Order By: Relevance
“…Our radiographic results agreed with two previous studies [ 30 , 41 ] which showed that AITFL repair had an important part in maintenance of syndesmotic reduction and the repair of AITFL was a reliable fixation. Furthermore, Kee J et al [ 5 ] shown that AITFL anatomical repair fixation has better radiographic outcomes and obviated the need for syndesmotic screw fixation in more than 80% of patients with syndesmotic instability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our radiographic results agreed with two previous studies [ 30 , 41 ] which showed that AITFL repair had an important part in maintenance of syndesmotic reduction and the repair of AITFL was a reliable fixation. Furthermore, Kee J et al [ 5 ] shown that AITFL anatomical repair fixation has better radiographic outcomes and obviated the need for syndesmotic screw fixation in more than 80% of patients with syndesmotic instability.…”
Section: Discussionmentioning
confidence: 99%
“…Syndesmosis screw fixation is the most popular treatment option for ankle fracture combined with syndesmotic injury [ 5 ]. However, this method is a static fixation and becomes controversial currently because it has a high complication concern [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, Littlechild advocated that consideration should also be given to reconstruction of the AITFL to augment the syndesmosis fixation, which may provide a stronger restoration of ankle stability compared to repairing the posterior inferior tibiofibular ligament (PITFL) in isolation, for example, by fixation of a posterior malleolus avulsion fracture [77]. In total, we found 13 publications recommending open repair and augmentation of the AITFL [2,11,20,28,58,77,80,98,119,135,140,167,170].…”
Section: Role Of the Aitflmentioning
confidence: 99%
“…Recently, there has been an interest in fixation of this "Chaput fragment" or "anterior malleolus", theorizing that fixation of the fractured anterior tibial fragment along with the attached anteroinferior tibiofibular ligament (AITFL) will restore tibial incisura and improve syndesmotic reduction. 3,4…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes, the syndesmotic injury can be accompanied with a bony avulsion. 3 When this involves the posterior malleolus (PM), the posteroinferior tibiofibular ligament (PITFL) has been shown to remain attached to the posterior malleolus fragment. Thus, reduction of this fracture fragment reconstructs the tibial incisura and restores syndesmotic reduction by effectively repairing the PITFL attachment.…”
Section: Introductionmentioning
confidence: 99%